Appendicitis (IntechOpen, 2023)
Acute appendicitis is considered to be the most common surgical emergency, with a lifetime risk of 7%. Appendicitis - Causes and Treatments is a comprehensive collection of works by experts who possess practical experience in the management of appendicitis. This publication is particularly relevant given that, during the Covid-19 pandemic, controversy over the management of appendicitis was highlighted. The book addresses the epidemiology and etiology of appendicitis, laparoscopic versus open appendicectomy, appendicitis in childhood, neglected appendicitis and perioperative nursing care. Furthermore, it discusses the evaluation and indications for surgical or non-surgical management (antibiotherapy) or both. Patient selection is a critical determinant of non-operative management, given the shortcomings of this approach, which requires active close observation to detect any deterioration indicating the need for an appendicectomy.